СОВЕРШЕНСТВОВАНИЕ АДМИНИСТРАТИВНОГО ЗАКОНОДАТЕЛЬСТВА В СФЕРЕ ВЗАИМОДЕЙСТВИЯ МЕЖДУ СУДЕБНО-ЭКСПЕРТНЫМИ УЧРЕЖДЕНИЯМИ - Контимирова, Виктория Викторовна (SUPREMANCE OF LAW, 2018)
The opinions of scientists on the ways of solving the problems of administrative and legal regulation of interaction between forensic institutions are analyzed. Attention is drawn to the inadequate state of administrative and legal regulation of interaction between forensic institutions of Ukraine, which necessitates the urgent need to improve the current legislation in this area. The author’s ways of reforming the administrative and legal regulation of interaction between forensic institutions are proposed, which should include the following stages: preparatory actions and the adoption of special regulatory legal acts that will directly regulate the issues of the outlined interaction. The characteristic is given to special forms of interaction within the specified stages.
Keywords: administrative and legal regulation; interaction; forensic institutions; independence; forms of interaction